Concentration‐dependent and surface‐assisted self‐assembly properties of a bioactive estrogen receptor α‐derived peptide. (22nd December 2014) - Ruggeri, Francesco Simone; Byrne, Cillian; Khemtemourian, Lucie; Ducouret, Guylaine; Dietler, Giovanni; Jacquot, Yves
<x xml:space="preserve">Abstract</x> We have synthesized a 17‐mer peptide (ERα17p) that is issued from the hinge region of the estrogen receptor α and which activates the proliferation of breast carcinoma cells in steroid‐deprived conditions. In the present paper, we show that at a concentration of 50 μM, it rapidly forms amyloid‐like fibrils with the assistance of electrostatic interactions and that at higher concentrations, it spontaneously forms a hydrogel. By using biophysical, spectral and rheological techniques, we have explored the structural, biophysical and mechanical characteristics of ERα17p with respect to fibril formation and gelation. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.